US Sailing (2008)
US SAILING was originally organized as the North American Yacht Racing Union (NAYRU) on October 30, 1897. As the National Governing Body for the sport of sailing, US SAILING's mission is to provide leadership for the sport of sailing in the United States. The organization works to achieve this mission through a wide range of programs and events, geared towards providing an equal level playing field for all sailors.